2012
DOI: 10.1155/2012/932725
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Effects of C-Peptide in Different Tissues

Abstract: Atherosclerosis is well known as an inflammatory disease that can lead to clinical complications such as heart attack or stroke. C-peptide as a cleavage product of proinsulin is in the last few decades known as an active peptide with a number of different effects on microvascular and macrovascular complications in type 2 diabetic patients. Patients with insulin resistance and early type 2 diabetes show elevated levels of C-peptide in blood. Several last findings demonstrated deposition of C-peptide in the vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…However, recent studies have revealed that it displays various functions in different cell types, although its receptor is unknown. These functions include binding to the pertussis-toxin-sensitive G-protein-coupled receptor on Swiss 3T3 fibroblasts, activation of the p38 protein kinase pathway in mouse lung capillary endothelial cells and activation of Na+/K+-ATPase in renal tubule segments [ 29 ]. At physiological concentrations, C-peptide seems to have a positive effect on chronic complications associated with T1DM, such as diabetic neuropathy and endothelial dysfunction, by providing protection against glucose-induced endothelial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have revealed that it displays various functions in different cell types, although its receptor is unknown. These functions include binding to the pertussis-toxin-sensitive G-protein-coupled receptor on Swiss 3T3 fibroblasts, activation of the p38 protein kinase pathway in mouse lung capillary endothelial cells and activation of Na+/K+-ATPase in renal tubule segments [ 29 ]. At physiological concentrations, C-peptide seems to have a positive effect on chronic complications associated with T1DM, such as diabetic neuropathy and endothelial dysfunction, by providing protection against glucose-induced endothelial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The start of hyperinsulinemia at the pre-IGT stage is an important and critical issue for early clinical care and prevention of long-term complication of type 2 diabetes mellitus. C-peptide, a structure cleaved from proinsulin, is equimolar with insulin and can bind to different cell receptors activating signaling pathways (6). It can deposit in the vascular walls of diabetic individuals and bring about pro-infl ammatory effect leading to atherogenesis (7).…”
Section: Discussionmentioning
confidence: 99%
“…That we did not include a pooled change from baseline analysis in our protocol could be seen as a limitation, but in order to perform this calculation we would have had to impute a standard deviation of the change, since this was not presented in the individual studies, and this may have introduced error into the results [ 12 ]. Several narrative reviews have been written on the physiological role of C-peptide and its effects on the kidney, peripheral nerves, vasculature, and inflammation, as well as its impact on intracellular signal transduction pathways in a variety of pathophysiological disease states [ 3 , 4 , 35 37 ]. Interestingly, the role of C-peptide in the setting of type 2 diabetes has not been well characterized.…”
Section: Discussionmentioning
confidence: 99%